Heart hypertrophy induced by levothyroxine aggravates ischemic lesions and reperfusion arrhythmias in rats - Yu Feng; Dai De-Zai; An Lu-Fan; Guo Xiu-Fang (Acta Pharmacologica Sinica, 2016)
AIM: To develop a cardiac hypertrophic model in rats. METHODS: Rats were i.p. levothyroxine 0.5 mg.kg-1.d-1 x 10 d. The action potentials of right papillary muscles were recorded by standard glass-microelectrode technique. The left coronary artery was ligated followed by reperfusion and the apparent infarcted zone (AIZ) was determined by tetracycline fluoresence, and the superoxide dismutase (SOD) activity and malondialdehyde (MDA) product in myocardium were also measured. RESULTS: In the rats treated by levothyroxine, the heart was hypertrophic and the action potential duration (APD) and effective refractory period (ERP) were prolonged, the APD20, APD50, APD90, and ERP were prolonged by 80%, 79%, 74%, and 68%, respectively. No changes in resting potential (RP), action potential amplitude (APA), and Vmax were produced. The incidence of heart arrest (8/8) and the risk of death (67 +/- 0) induced by ischemia-reperfusion in rats with hypertrophic heart was higher than those in normal rats (4/10 and 44 +/- 19, respectively). The AIZ was expanded markedly in hypertrophic heart, and attenuated by lidocaine and propranolol. CONCLUSION: Levothyroxine-induced heart hypertrophy is a suitable model for severe ischemia and arrhythmias in rats.